Venoarterial flow index steadily improves after endovenous laser treatment of the great saphenous vein - Rass, Knuth; Pasquini, Chantal; Hamsch, Corinna; GräBer, Stefan; Frings, Norbert; Tilgen, Wolfgang (Dermatologic surgery, 2010)
BACKGROUND - Endovenous laser treatment (EVLT) is a minimally invasive procedure to ablate varicose veins. The venous arterial flow index (VAFI) represents a quantitative duplex ultrasound parameter to characterize venous hemodynamics, which has not been investigated in EVLT so far. - OBJECTIVE - To analyze the hemodynamic improvement of EVLT of the great saphenous vein (GSV) according to VAFI measurement. - MATERIALS AND METHODS - One hundred thirty-three participants with complete GSV insufficiency were treated with 810-nm EVLT. VAFI as a ratio of venous and arterial flow volumes of the common femoral vessels and digital photoplethysmography (DPPG) were assessed before and 3 (n=129) and 12 months (n=71) after EVLT. - RESULTS - EVLT was performed with an energy fluence of 22.5 J/cm2, resulting in an occlusion rate of 98.4%. Duplex recurrence rates were 9.4% at 3-month and 15.5% at 12-month follow-up. VAFI significantly improved from 1.395 to 1.242 and 1.167 (p<.001) 3 and 12 months after EVLT. Venous refilling time (DPPG) accordingly increased from 20.0 to 36.9 seconds (p<.001) 3 months postoperatively. - CONCLUSION - EVLT improves hemodynamic alterations in people with incompetent GSVs as demonstrated using VAFI and DPPG. VAFI might be a suitable diagnostic tool to quantify venous hemodynamics in people with varicose veins.